(untitled) (Heteroglossia – studia kulturoznawczo-filologiczne, 2023)
The article aims to show the role that the ancient myth of the Hyperboreans played in the German superpower ideology. In this aspect, the opinions of fourteen German scholars from 1616 to 1875, i.e. over a period of 259 years, were analysed. These opinions prove that the Hyperborean myth was used to emphasize the ethical and moral values of the German nation. In turn, these values were to prove that Germany’s aspirations to the role of a superpower were right. Referring to the Hyperborean myth was at the same time referring to the Hellenic idea of the chosen nation. This, in turn, was a justification for the German feeling of superiority over other nations. This conviction grew gradually over several generations and was a source of German national pride. The most important elements of this pride were briefly summarized by A. Riese: „Gerechtigkeit, Tapferkeit, Freiheit”. This phrase can probably be considered a German response to the French, revolutionary postulate – „Liberté, Égalité, Fraternité”.